2020
DOI: 10.3390/ijms21228508
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Non-Coding RNAs in Response to Nitrogen Availability in Plants

Abstract: Nitrogen (N) is an essential nutrient for plant growth and development; therefore, N deficiency is a major limiting factor in crop production. Plants have evolved mechanisms to cope with N deficiency, and the role of protein-coding genes in these mechanisms has been well studied. In the last decades, regulatory non-coding RNAs (ncRNAs), such as microRNAs (miRNAs), small interfering RNAs (siRNAs), and long ncRNAs (lncRNAs), have emerged as important regulators of gene expression in diverse biological processes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 139 publications
0
10
0
Order By: Relevance
“…Moreover, many N-responsive transcription factors and functional genes have been identified, and their functions in N-associated metabolism and growth have been revealed (Hackenberg et al, 2013;Dash et al, 2015Dash et al, , 2016. With the rapid development of high-throughput sequencing technology and efficient big data technology, an increasing number of nonprotein coding genes, especially microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), have been identified and shown to participate in the N metabolic response of woody plants (Li et al, 2016;Zuluaga et al, 2017;Lu et al, 2019;Fukuda et al, 2020;Zhou and Wu, 2022a). For example, miR167, miR169, miR393 and miR396 were inhibited by N starvation (Gifford et al, 2008;Pant et al, 2009;Vidal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many N-responsive transcription factors and functional genes have been identified, and their functions in N-associated metabolism and growth have been revealed (Hackenberg et al, 2013;Dash et al, 2015Dash et al, , 2016. With the rapid development of high-throughput sequencing technology and efficient big data technology, an increasing number of nonprotein coding genes, especially microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), have been identified and shown to participate in the N metabolic response of woody plants (Li et al, 2016;Zuluaga et al, 2017;Lu et al, 2019;Fukuda et al, 2020;Zhou and Wu, 2022a). For example, miR167, miR169, miR393 and miR396 were inhibited by N starvation (Gifford et al, 2008;Pant et al, 2009;Vidal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, N-dependent changes in root architecture are found in many plant species (56) and this has consequences on other root-dependent traits such as water acquisition. Concomitantly, it has been observed that N starvation changes the expression of multiple lncRNAs in arabidopsis (57), poplar (58), barley (59), maize (60) and rice (61). For example, two antisense lncRNAs are significantly induced in rice roots upon N starvation (61) and may regulate the AMMONIUM TRANSPORTER 1 (AMT1) gene that participates in N assimilation (62).…”
Section: Lncrnas-mediating Nutrient Homeostasis and Coordination Of R...mentioning
confidence: 99%
“…The nitrate responsive microRNA393 (miR393): AFB3 module can integrate external nitrate availability and the internal N status in plants [ 40 ]. The roles of non-coding RNAs in response to N availability in plants have also been reviewed recently [ 41 ]. In addition, NRT1.1 has been shown to be involved in nitrate-repressed auxin transport [ 42 ].…”
Section: Regulation and Interaction Of C And N Metabolismmentioning
confidence: 99%